Balanced Scorecard Model for Hazards Risk Management at Limpopo River Basin A Country Participatory Approach for MCDA with Scenario Planning - Mondlane, Avelino Isaias; Hasson, Karin; Popov, Oliver (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper focuses on the application of both Balanced Scorecard (BSC) conceptual framework and Multi-criteria Decision Analysis (MCDA) a tool for Scenario Planning as a tool for Strategic Decision Thinking, on hazard risk management within Limpopo River Basin. We discuss best practices in four main domains areas, namely Politic (as pool for country raking worldwide), Economic, Social Development and Technology and how they can contribute to build a viable scenario for the management of the basin.